External forces acting in direction of travel and their relation to energy dissipation in slalom - Gilgien, M. (2008)
The share of literature describing the kinetics of alpine skiing is limited in general, but especially for the discipline slalom. In recent kinematical studies energy dissipation, a measure for the quality of skiing, turned out having instantaneous statistical relations to key movement characteristics as well as to ranges of motion and performance measured in time. However scientific studies addressing these relations from a functional perspective, investigating how movement characteristics are related to kinetics and energy dissipation are lacking in the literature. The present study foremost attempts to broaden the knowledge about the external forces acting on the skier in direction of travel in the discipline slalom. Further the relation between these forces and energy dissipation is investigated to establish a basis for the description how movements are related with kinetics and energy dissipation.